(untitled) (Iranian Journal of Kidney Diseases, 2021)
Introduction. Vesicoureteral reflux (VUR) is a well-known risk factor for urinary tract infection (UTI). We aim to define diagnostic values of kidney ultrasonography (US) as a predictor of VUR and high grades VUR in children presented by UTI. Methods. This retrospective study was conducted during October 2003 to 2016. Children aged ≤ 18 years with history of UTI who had underwent kidney US and direct cystography [voiding cystourethrography (VCUG) or radionuclide cystography (RNC)] enrolled in the study. Diagnostic values of hydronephrosis, hydro ureter, renal scaring, hydroureteronephrosis, decreased kidney size and abnormal kidney US for diagnosis of VUR and high grades VUR (grades IV-V) were evaluated. Results. Hydro-ureter, renal scaring, and hydroureteronephrosis were significantly more prevalent in VUR+ versus VUR- cases, also in higher grades compared with lower grades (grades I-III) VUR (P < .05 for all). Additionally, hydronephrosis was more common in VUR+ compared with VUR- patients (P < .0001). As a predictor of VUR and higher grades of VUR, abnormal kidney US had the highest sensitivity (24.87% and 40.84%, respectively), abnormal kidney US and hydro ureter reached the highest NPV (70.42% and 81.27%, respectively), hydroureteronephrosis and hydro ureter showed the highest accuracy (68.51% and 82.21%, respectively) . Conclusion. Kidney US is a valuable screening test, abnormal renal US significantly increases the probability of VUR and high grades VUR , but if used as the only screening test , about 2/3 and 1/3 and 20% of VUR , high grades VUR and grade V VURs will be missed. DOI: 10.52547/ijkd.5966